KINERJA MANAJEMEN PERSEDIAAN BARANG DAGANGAN PT. ARTHA DINAMIS SENTOSA BALI - Putra, Dewa Gede Eka Narendra; Purnawati, Ni Ketut (E-Jurnal Manajemen, 2018)
Inventory is an expensive and important asset for the company, so that inventory does not burden the company's finances and affects the smoothness of its production activities, so it is important to carry out inventory control. This study aims to know how the system of inventory control merchandise that should be done by PT. Artha Dinamis Sentosa Bali, and find out whether the inventory control system is efficient or not. The data used is the quantitative and qualitative data obtained by conducting interviews to the parties related to inventory and observation on the object under study. Data analysis technique used is descriptive analysis technique explain systematically with stages are: ABC Analysis, EOQ Determination, Determination of savety stock, Determination of Re-Order Point, determination of maximum inventory, calculate Inventory Turnover and calculate total cost. The results show the merchandise inventory system that should be done is to classify the ABC analysis method, then determine the EOQ, determine the Savety Stock and determine the Reorder Point on each inventory item. The company's inventory control system is not efficient yet because the total cost by controlling with EOQ is Rp 100,175,045, lower by total inventory cost using inventory control method by company amounting to Rp 160,186,971. Keywords:   ABC Analysis, Economic Order Quantity, Savety Stock, Reorder Point, Inventory Turnover.